32.M. Workshop: Mig-HealthCare project: Reducing health inequalities of vulnerable migrants in Europe. (30th September 2020) - ,; ,
Abstract: This MigHealthCare Workshop will be a forum to present and discuss the project's final results with a wide range of health and social care professionals working on the field of migrant/refugee health. The Mig-HealthCare project is a collaboration of 14 partners, among them universities, national authorities and NGOs from 10 countries across Europe (Greece, France, Malta, Germany, Austria, Italy, Cyprus, Spain, Sweden and Bulgaria). The major aim of the project is to reduce health inequalities and improve the integration of vulnerable migrants and refugees into local communities in Europe. The project is co-funded by the III Health Programme of the European Commission from 2017-2020. The Mig-HealthCare project addresses the need for structural changes in the health systems to respond to the unmet needs of vulnerable migrants and refugees in Europe and promotes community-based care. Community-based health care has proven to be effective in reducing health inequalities in health, as well as improving accessibility to appropriate care. For this purpose, the consortium has produced an evidence-based Roadmap and Toolbox to reorient health care services to a community level which is a user-friendly online application focusing on the key steps for optimal health care delivery to migrants and refugees. In this regard and as part of these operative tools, within the Mig-HealthCare project, effective community-based care interventions focused on health promotion or prevention were designed and piloted in 8 different contexts and countries. As main results of the MigHealthCare project, the Roadmap and Toolbox comprise both the necessary factors that health policy and practice need to deliver culturally competent care as well as the particular health issues especially faced by migrants and refugees in order to better prepare public health response. Key messages: Community-based care for vulnerable migrants and refugees has proven to be effective in reducing health inequalities. Evidence on the drivers of the success or failure of health promotion strategies for migrants and refugees should be considered when planning interventions.